2022
DOI: 10.1021/acs.biochem.1c00774
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Triggered μ-Peroxodiiron(III) Intermediate in the 4-Chloro-l-Lysine-Fragmenting Heme-Oxygenase-like Diiron Oxidase (HDO) BesC: Substrate Dissociation from, and C4 Targeting by, the Intermediate

Abstract: The enzyme BesC from the β-ethynyl-l-serine biosynthetic pathway in Streptomyces cattleya fragments 4-chloro-l-lysine (produced from l-Lysine by BesD) to ammonia, formaldehyde, and 4-chloro-l-allylglycine and can analogously fragment l-Lys itself. BesC belongs to the emerging family of O2-activating non-heme-diiron enzymes with the “heme-oxygenase-like” protein fold (HDOs). Here, we show that the binding of l-Lys or an analogue triggers capture of O2 by the protein’s diiron­(II) cofactor to form a blue μ-perox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…Assembly of the O 2 -reactive BesD•Fe II •2OG• l -Lys•Cl complex (hereafter the quinary complex) could have a preferred or even obligatory binding order. We probed the formation of the initial binary complex, BesD•Fe II , by ferrozine-chelation experiments , to find a K D of 3.7 ± 0.7 μM (Figure S5). Next, in titrations monitoring the ∼500 nm MLCT band, we found that binding of 2OG to the BesD•Fe II binary complex is associated with a K D , K 2OG , of 14 ± 5 μM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assembly of the O 2 -reactive BesD•Fe II •2OG• l -Lys•Cl complex (hereafter the quinary complex) could have a preferred or even obligatory binding order. We probed the formation of the initial binary complex, BesD•Fe II , by ferrozine-chelation experiments , to find a K D of 3.7 ± 0.7 μM (Figure S5). Next, in titrations monitoring the ∼500 nm MLCT band, we found that binding of 2OG to the BesD•Fe II binary complex is associated with a K D , K 2OG , of 14 ± 5 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Although we viewed the idea of reversible binding of substrates in an intermediate state of sufficient potency to cleave an unactivated C−H bond as surprising, we did recently demonstrate such lability in the substrate-triggered peroxodiiron(III) intermediate state in the diiron enzyme BesC, which fragments 4-Cl-L-Lys and L-Lys�putatively by abstracting hydrogen from C4�in the β-ethynylserine biosynthetic pathway. 30 Synergistic Binding of Cl − and L-Lys in the Chloroferryl Intermediate State. In light of the demonstrated binding synergy between the anion and prime substrate in the Fe II state of BesD, we further evaluated the possibility of reversible substrate association in the intermediate state by testing for an interplay between the Cl − and L-Lys concentrations in the kinetics of decay of the chloroferryl intermediate and its partitioning between productive and unproductive pathways.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30,37 Indeed, HDOs have emerged as a superfamily of non-heme diiron enzymes, with over >10 000 HDO sequences identified bioinformatically. 38 In addition to SznF, a growing member of HDOs has been characterized recently, including fatty acid oxidase UndA, 17−19 the 4-chloro-L-lysine-fragmenting BesC, 15,16 and other N-oxygenases RohS, 46 HrmI, 47 and BelL. 48 In the HDO domain of SznF, two irons are bridged by Glu215; one iron (donated as Fe2) is ligated by Glu189, His225, and His311, while the other iron (donated as Fe1) is ligated by Glu281, His318, and Asp315.…”
Section: Introductionmentioning
confidence: 99%
“…One superfamily of metalloenzymes can utilize non-heme diiron active sites for O 2 activation and reductions . These non-heme diiron enzymes catalyze many types of reactions, such as the challenging C–H activations occurring in sMMO, BesC, , UndA, PtmU3, and Δ9 Desaturase, epoxidation of double bond occurring in BoxB, , N-oxygenation occurring in AurF and CmlI, as well as N-hydroxylation occurring in SznF. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation